Development of a Problem-Based Learning Physics Module on Uniform Circular Motion to Support Students’ Critical Thinking Skills - Yunita Hapriza; Hamdi Akhsan; Kistiono Kistiono (Department of Physics Education, Universitas Mataram, 2026)
Physics instruction on Uniform Circular Motion (UCM) is often perceived by senior high school students as abstract and difficult to comprehend due to its limited connection with real-life phenomena. This study aims to develop a physics teaching module based on Problem-Based Learning (PBL), integrated with simple demonstrations using coins and strings and supported by investigative student worksheets (LKPD). The research employed the Research and Development (R&D) method using a modified ADDIE model consisting of analysis, design, development, and evaluation stages. The study focused on examining the validity and practicality of the developed module. Evaluation was conducted through expert reviews involving three validators (a physics content expert, a pedagogy expert, and an instructional design expert), a one-to-one trial with three students, and a small-group trial with nine Grade XI students from SMAN 13 Palembang. The validation results indicate that the module achieved an average score of 88.33%, categorized as very valid. Meanwhile, the practicality test produced an average score of 91.7%, indicating that the module is very practical to use in learning activities. The module facilitates learning through the PBL stages, including problem orientation, investigation through demonstrations and videos, group discussion, and reflection. Although the effectiveness of the module in improving students’ conceptual understanding and critical thinking skills has not yet been empirically tested, the results indicate that the developed module is valid and practical and has the potential to support meaningful learning experiences on the topic of Uniform Circular Motion.